Screening and Identification of Antagonistic Strain HAS against Sporisorium scitaminea Sydow - Guoru, Xiong; Gengfeng, Zhao; Suran, Wu; Cuilian, Feng; Wenwei, Cai; Shuzhen, Zhang (Plant Diseases and Pests(植物病虫害研究：英文版), 2014)
The present study was to screen and identify a biocontrol strain with antagonistic effect against Sporisorium scitaminea Sydow. 16 S rDNA gene fragments were amplified by universal primers P0 and P6. The results showed that 16 S rDNA gene fragment with the size of 1 533 bp was obtained,and its sequence had the homology of 99% with the sequence of Bacillus subtilis. The morphological characteristics of the strain were as follows： the mycelium of strain HAS was short-rod shape,and could move; Gram staining was positive; 3% KOH solubility test was negative; flagellum was grown around the cells; spores were grown in the middle,elliptic,and cysts were slightly swelled. The strain was preliminarily identified as B. subtilis. Dual culture with pathogenic fungi showed that the strain had good inhibitory effect against various pathogenic fungi causing diseases on sugarcane and other crops. Therefore,strain HAS isolated in the study was identified to be B.subtilis,which had good control effect against S. scitaminea.